2022
DOI: 10.14203/oldi.2022.v7i2.400
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penggunaan Pakan Buatan Berbahan Baku Tepung Makroalga Hijau Ulva sp. Terhadap Pertumbuhan Yuwana Abalon Haliotis squamata

Abstract: Abalon merupakan salah satu sumberdaya laut yang memiliki potensi untuk dibudidayakan di Indonesia karena merupakan salah satu biota yang memiliki nilai ekonomi tinggi. Keberhasilan budidaya abalon salah satunya ditentukan oleh ketersediaan pakan termasuk ketersediaan pakan formula. Pemanfaatan tepung Ulva sp. sebagai bahan campuran pada formulasi pakan abalon memiliki peluang untuk dikembangkan guna mendukung keberhasilan budidaya abalon. Oleh karena itu, penelitian ini bertujuan untuk mengetahui pengaruh pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Ulva reticulata is abundantly found in several Indonesian waters, including Bali, East Nusa Tenggara, and Sulawesi, but it has not been used for aquaculture activities (Meiyasa et al 2020). Several studies have reported that Ulva rigida, Ulva chlorate, Ulva lactuca, and Ulva intestinalis can serve as alternative nutritional feed ingredients, promoting improvement in fish growth, reproduction, and health (Corral-Rosales et al 2019;Van doan et al 2019;Klongklaew et al 2021;Rahim et al 2021;Ridwanudin et al 2022). The use of this species has been confirmed to be non-toxic for fish physiology (Madibana et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ulva reticulata is abundantly found in several Indonesian waters, including Bali, East Nusa Tenggara, and Sulawesi, but it has not been used for aquaculture activities (Meiyasa et al 2020). Several studies have reported that Ulva rigida, Ulva chlorate, Ulva lactuca, and Ulva intestinalis can serve as alternative nutritional feed ingredients, promoting improvement in fish growth, reproduction, and health (Corral-Rosales et al 2019;Van doan et al 2019;Klongklaew et al 2021;Rahim et al 2021;Ridwanudin et al 2022). The use of this species has been confirmed to be non-toxic for fish physiology (Madibana et al 2017).…”
Section: Introductionmentioning
confidence: 99%